Knowledge and practices on lymphatic filariasis in patients with filarial morbidity in an endemic area in Northeastern Brazil - Marcondes, Márcia; Brandão, Eduardo; Oliveira, Paula; Bonfim, Cristine; Miranda, Tereza; Rodrigues, Heloísa; Braga, Cynthia; Rocha, Abraham (Frontiers in Tropical Diseases, 2024)
BackgroundLymphatic filariasis (LF) is a stigmatizing and debilitating disease that represents a significant global public health challenge. Information regarding the knowledge and practices of individuals with filarial morbidities is limited, and this understanding is crucial for the implementation of effective control strategies. This study aimed to investigate the knowledge and practices of individuals with filarial morbidity residing in two intervention areas of the Elimination Program in the city of Olinda, Brazil.MethodsA cross-sectional study was carried out with residents who reported filarial morbidity in 2010, four years after the start of mass drug administration, in the intervention areas of the LF Elimination Program in the city of Olinda, Brazil. The knowledge and practices of patients with reported filarial morbidity in an endemic area were scrutinized using a semi-structured questionnaire to collect pertinent information. Data were analyzed utilizing the R language version 3.6.1.ResultsFilarial morbidity was reported in 338 patients. Dermatolymphangioadenitis emerged as the most frequently reported clinical form (50.9%). Mosquito bites were the most commonly cited form of transmission, accounting for 296 cases (87.6%). Approximately 80% (266) confirmed the adoption of prevention measures. Participants reported that the treatment involved the administration of medication. The existence of a cure for parasitosis was indicated by 212 subjects (62.7%).ConclusionsIndividuals with reported filarial morbidity exhibit varying levels of conceptions, knowledge, and practices regarding the disease, despite residing in an endemic area and receiving consistent visits from family health teams. Health services must identify shortcomings in this approach to minimize disparities, thereby enabling health education to effectively contribute to disease control and elimination in the municipality.